(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This article aims to reflect on the importance of migratory movements for the construction of a history of puppet theater in Brazil and Argentina. In this sense, we start from the premise that the historian of this scenic language must take into account the concept of “connected history” in order to create a “national history”, since international connections, which occur mainly through migratory movements, are fundamental for a better understanding of the trajectory of puppet theater in these countries.